INTEGRATION OF TECHNOLOGY IN IMPROVING THE PROFESSIONALISM OF ISLAMIC RELIGIOUS EDUCATION TEACHERS - Mulasi, Syibran; Susanna , Susanna; Jannah, Misbahul; Syibran Mulasi (Program Studi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2025)
Technological developments have significantly impacted various aspects of life, including education. This research aims to analyze the role of technology in increasing the professionalism of Islamic Religious Education (PAI) teachers. The research uses qualitative methods with a literature study approach, which involves collecting data from various sources such as scientific journals, books, articles, and related documents. Data analysis used a content analysis approach to identify the main themes and relationships between technology and PAI teacher professionalism. The research results show that technology has great potential in the professionalism of PAI teachers in utilizing technology through various innovations, such as interactive media, digital learning applications, and e-learning platforms. Technology helps teachers deliver material more interestingly and efficiently, and supports students to learn independently and collaboratively. In addition, the integration of technology in the professional development of PAI teachers has been proven to increase students' understanding of religious values, strengthen their character, and motivate them to be active in the learning process. This research concludes that optimal use of technology can be a solution to overcome challenges in increasing the professionalism of PAI teachers. It is hoped that these findings will become a reference for developing learning strategies that are more innovative and relevant to the educational needs of the 21st century.